PENGEMBANGAN KEPRIBADIAN KONSELOR BERBASIS ASMAUL HUSNA DALAM PELAYANAN KONSELING - Ardimen Ardimen (UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to develop the personality of “asmaul-husna” -based counselor. Counselors who have competence good personality, friendly, and empathetic santun certainly be role models for clients. Personality counselor is supporting the process and results of counseling and assisting clients in exploring, developing, and in facilitating its development. The approach used in this study is the study documentation of the analysis of references and discuss research results and study counselor personality of “asmaul-husna” as a personality basis counselor. Among the values of “asmaul-husna” can be realized in treatment counselor when dealing with clients, namely: has the properties (1) to love, (2) compassionate, (3) rule / leader, (4) has sanctity, (5) giving welfare, ( 6) security provider, (7) custodian, (8) 'manly', (9) 'strong', (10) is able to create / initiative, (11) was able to achieve balance, (12) the opening of grace, (13) clement / forgiving, (14) had committed, (15) the giver of gifts, (16) ar-Razzaq, (17) the opening of grace, (18) has a knowledge / own knowledge, (19) which paved, (20) which glorify, and (22) who listen.Key words: personalities counselor, ‘asmaul-husna, counseling and counselor profession.